1999
DOI: 10.1212/wnl.53.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of unilateral and bilateral subthalamic nucleus deep brain stimulation

Abstract: Bilateral STN DBS improves parkinsonism considerably more than unilateral STN DBS; bilateral simultaneous electrode implantation may be the most appropriate surgical option for patients with significant bilateral disability. Unilateral STN DBS results in moderate improvement in all aspects of off-period parkinsonism and improves tremor as much as is typically reported with DBS of the ventral intermedius nucleus of the thalamus (Vim). For this reason, STN DBS may be a more appropriate choice than Vim DBS or tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
138
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(167 citation statements)
references
References 24 publications
(5 reference statements)
25
138
1
2
Order By: Relevance
“…Similar results were observed by Samii et al, who scheduled patients with advanced PD for staged bilateral STN DBS (19). Unilateral STN DBS resulted in a 25% improvement of the motor UPDRS score with a further 53% improvement when an additional DBS lead was implanted (19 (5,22). The effects of unilateral STN DBS are not primarily restricted to the contralateral side, however most authors also report benefits in the ipsilateral and axial features (although the improvements tend to be only temporary (22,23,26).…”
Section: █ Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were observed by Samii et al, who scheduled patients with advanced PD for staged bilateral STN DBS (19). Unilateral STN DBS resulted in a 25% improvement of the motor UPDRS score with a further 53% improvement when an additional DBS lead was implanted (19 (5,22). The effects of unilateral STN DBS are not primarily restricted to the contralateral side, however most authors also report benefits in the ipsilateral and axial features (although the improvements tend to be only temporary (22,23,26).…”
Section: █ Discussionsupporting
confidence: 73%
“…Moreover, unilateral STN stimulation procedures are less invasive than bilateral simultaneous STN procedures (2,4,5,8,17,19,22,23). Bearing in mind all of the above facts, we aimed to operate on PD patients with the asymmetry of PD symptoms.…”
mentioning
confidence: 99%
“…One study measured the effects of ipsilateral, contralateral or bilateral STN DBS and found that contralateral and bilateral stimulation provided significant benefit in UPDRS ratings and timed hand movement tasks (Purdue pegboard and timed hand tapping). Ipsilateral stimulation did not significantly improve bradykinesia, tremor or rigidity as measured with the UPDRS or by Purdue pegboard test (Kumar et al, 1999). In that study, ipsilateral stimulation did improve timed hand tapping by 19% compared to 29% with contralateral stimulation and 54% with bilateral stimulation.…”
mentioning
confidence: 69%
“…The mechanism of this bilateral effect is unknown, although transhemisphere interactions at thalamic or cortical levels may be involved (Parent and Hazrati, 1995;Eidelberg et al, 1996). Augmentation of network modulation by contralateral stimulation supports the utility of bilateral DBS interventions, even in asymmetrical parkinsonism (Kumar et al, 1999).…”
Section: Metabolic Changes With Stn Stimulationmentioning
confidence: 81%